A comparative study of Grewia bicolor Juss. and Grewia flava DC - Bartsch, Silke (Department of Biological Sciences, 2017)
Grewia bicolor and Gewia flava have been recognized by earlier authors as separate species on the basis of the shape of the leaf base, the number of flower stalks on the peduncle and reticulate venation of the tertiary veins. These two "species" are extremely variable, and often characters from G. bicolor and G. flava are exhibited on the same specimen. This study aims at evaluating the distinction between the two "species", thereby testing whether they should be recognized as separate taxa, and if so, which characters can be used to delimit G. bicolor and G. flava. Numerical phenetic analyses of 11 characters investigated from 211 herbarium specimens revealed that the two "species" cannot be differentiated by the traditional characters. Univariate analysis showed that the diagnostic characters that have been used to date show continuous variation. Thus G. bicolor and G. flava cannot be recognized as separate species.